PERISTILAHAN DALAM â€œNUBAK ADATâ€ ( TRADISI MENANGKAP IKAN) MASYARAKAT MELAYU KETAPANG: PENDEKATAN ETNOLINGUISTIK - Darma, Adip; Salem, Laurensius; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractResearch on adat nubak is an effort to explore cultural treasures as preservation and inventory for the enrichment of regional languages and Indonesian. This study aims to find out how terminology in adat nubak (tradition of catching fish) Ketapang Malay community. This study uses the observation method, a form of qualitative research using an ethnolinguistic approach in the context of the use of language in an area that is related to the culture of society. The terminology contained in this research is in the form of tools, processes, time, actors, places, and spells. Analysis of terms, namely monomorfemis, polymorphemis, and phrases. In addition, this study also describes the meaning of terminology in the traditional nubak tradition based on lexical meaning and cultural meaning. Based on the research conducted, the researchers succeeded in gathering 54 terminologies in the traditional nubak of the ketapang Malay community consisting of 20 tool terms, 17 process terms, 2 time terms, 6 place terms, 3 terms of perpetrators, 6 terms of mantra. The term analysis of the form of monomorfemis 21, the term polymorphemis 21 and the phrase 12 lexical terms and meanings and cultural meanings contained therein.Keywords: Ethnolinguistics, Ketapang, Malay, Nubak Adat,Â  Terminology